PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BKPSDM KABUPATEN SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Ricky Hidayat; Ika Wahyuni; Minullah Minullah (Fakultas Ekonomi dan Bisnis, 2025)
State Civil Apparatus (ASN), as civil servants, carry out the state's duty to serve the public. ASN are required to be responsible and possess good attitudes and mental qualities so that development objectives can be achieved. ASN require effective human resource development to improve the quality of public service. Human resource development for ASN is realized through the implementation of a code of ethics and a code of conduct. One of the codes of ethics and a code of conduct, as stipulated in Law No. 5 of 2014 concerning State Civil Apparatus, Article 5, paragraph 2b, requires carrying out duties with care and discipline. Human Resources (HR) encompass the inherent values of each individual and their ability to contribute to society. A person's mental and physical capacity, as well as their behavior, are resources. Human actions are shaped by the environment and the people they work with, and people work because they seek satisfaction. The purpose of this study is to analyze and test the influence of leadership, work environment, and work discipline on employee performance at the Situbondo Regency Human Resources Development Agency (BKPSDM), with job satisfaction as an intervening variable. This research is quantitative. The population used in this study was 42 employees, excluding leaders. The sampling technique used was simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Method – Partial Least Squares (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application indicate that leadership has a significant positive effect on job satisfaction. The work environment has a significant positive effect on job satisfaction. Work discipline has a significant positive effect on job satisfaction. Leadership has a positive but insignificant effect on performance. The work environment has a positive but insignificant effect on performance. Work discipline has a significant positive effect on performance. Job satisfaction has a significant positive effect on performance. Leadership has a significant positive effect on performance through job satisfaction. The work environment has a significant positive effect on performance through job satisfaction. Work discipline has a significant positive effect on performance through job satisfaction.